3-Move undeniable signature scheme - Kurosawa, Kaoru; Heng, Swee Huay (Springer Berlin Heidelberg, 2005)
In undeniable signature schemes, zero-knowledgeness and non-transferability have been identified so far. In this paper, by separating these two notions, we show the first 3-move confirmation and disavowal protocols for Chaum's undeniable signature scheme which is secure against active and concurrent attacks. Our main observation is that while the signer has one public key and one secret key, there exist two witnesses in the confirmation and disavowal proofs of Chaum's scheme.